A new species of Clypeocaenis Soldán 1978 (Ephemeroptera: Caenidae) from Tamil Nadu, India - Srinivasan, Pandiarajan; Sivaruban, T.; Barathy, S.; Isack, Rajasekaran; Jacobus, Luke M. (Zootaxa, 2022)
Clypeocaenis malzacheri sp. nov. is described from the Kottakudi River in southern India, based on larvae and eggs. Clypeocaenis malzacheri sp. nov. appears to be closely related to C. bisetosa Soldán. The new species is distinguished from this species and other congeners based on the structure of the frons; the structure, setation, and maculation of legs; the shape and orientation of the abdominal tergum II projection; and by the shape and denticulation of abdominal sternum IX. Updated couplets for an identification key to Clypeocaenis larvae in the Indomalayan region are provided. The total number of Clypeocaenis species is thereby increased to twelve in the world and seven in India.